Propuesta para la reutilización de purgas provenientes de las torres de enfriamiento de O-I Peldar, en uno de los procesos de tratamiento térmico de la fabricación del vidrio. (2020)
The development of this proposal will begin with the diagnosis of the different heat treatment processes used in the manufacture of glass at the OI Peldar Zipaquirá plant, the process for which the purge waters will be reused is established by means of a matrix selection, which is based on the cooling system with the highest water consumption. Subsequently, a quantification of the water that comes out of the cooling systems is continued, and with this data we will proceed to characterize a mixture of the purges of the 6 cooling towers that maintain continuous purge in the plant, where 5 critical variables will be determined (pH, conductivity, hardness, total dissolved solids and turbidity) that will characterize these wastewater. For this, physicochemical analyzes will be carried out in the laboratory of the O-I Peldar water plant to obtain data on these variables. Once the characterization has been carried out, we proceed to verify the quality of water to be reached, so that the water from the purges can be reused according to the requirements of the selected cooling system. It should be noted that the selection of said quality will be made in accordance with the water parameters required in the safety data sheet of the different chemicals that react in the system.